Impacts of differing community composition on flowering phenology throughout warm temperate, cool temperate and xeric environments. Issue 7 (6th March 2014) - Park, Isaac W.
Abstract Aims Flowering phenology is well documented to restrict the distribution of many plant species. However, community‐level shifts in flowering time may occur either through exclusion of species with unsuitably early or late flowering for local conditions (composition‐derived phenological shifts) or through intraspecific phenological responses to climate variations over space. Although these mechanisms have quite different ecological implications, the relative contribution of composition‐derived phenological shifts remains largely unknown. Therefore, determining the magnitude of composition‐derived phenological variation is crucial for understanding the relationship between phenology and community assemblage over space, and for predicting the impacts of future climate change. This study will evaluate the contributions of compositional differences to spatial variation in community‐level flowering times throughout the early, mid and late portions of the growing season and across a variety of temperate environments. Location Continental United States. Methods This study develops novel herbarium‐based methods to separate intraspecific phenological variations over space from changes in flowering time derived from differences in community composition. Results Although typically smaller than intraspecific variations, composition‐derived shifts in flowering time explained up to 49.3% of overall phenological variation. Composition‐derived changes in flowering time among late‐flowering species also explained the greatest proportion of overall variation and were the most responsive to differing climate conditions. Xeric regions also exhibited composition‐derived phenological shifts that were stronger and more closely tied to climate conditions (R2 up to 0.553) than other regions. Main conclusions These results indicate that interspecific differences in flowering time play a significant role in determining the composition of the plant community over space. However, the impact of flowering phenology on community assemblage varies considerably among seasons and climate regions, and appears to be strongest among xeric regions and among late‐flowering species.